ORGANIZATION OF INTERNAL AUDIT AT ENTERPRISES THEORETICAL AND METHODOLOGICAL ASPECTS OF CREATION (British Journal of Global Ecology and Sustainable Development, 2023)
This article discusses the theoretical and methodological aspects of the organization of financial control at enterprises and organizations, examines the literature on the topic of the study and gives relevant conclusions and suggestions.